2015
DOI: 10.1161/circulationaha.114.013878
|View full text |Cite
|
Sign up to set email alerts
|

O -Linked β- N -Acetylglucosamine Transferase Directs Cell Proliferation in Idiopathic Pulmonary Arterial Hypertension

Abstract: Background Idiopathic Pulmonary arterial Hypertension (IPAH) is a cardiopulmonary disease characterized by cellular proliferation and vascular remodeling. A more recently recognized characteristic of the disease is dysregulation of glucose metabolism. The primary link between altered glucose metabolism and cell proliferation in IPAH has not been elucidated. We aimed to determine the relationship between glucose metabolism and smooth muscle cell proliferation in IPAH. Methods and Results Human IPAH and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 56 publications
5
52
1
Order By: Relevance
“…Previous analysis of the 3Ј-UTR of OGT revealed that it is one of the most highly regulated glycogenes (41). O-GlcNAc, the epitope controlled by this enzyme, is involved in cell proliferation (42,43), consistent with targeting by miR-424. Thus, further exploration of the interaction between miR-424 and OGT in alternate biological systems is warranted.…”
Section: Discussionmentioning
confidence: 94%
“…Previous analysis of the 3Ј-UTR of OGT revealed that it is one of the most highly regulated glycogenes (41). O-GlcNAc, the epitope controlled by this enzyme, is involved in cell proliferation (42,43), consistent with targeting by miR-424. Thus, further exploration of the interaction between miR-424 and OGT in alternate biological systems is warranted.…”
Section: Discussionmentioning
confidence: 94%
“…Collectively, this report suggests that altered BMP signaling in IPAH can result independent of BMPR2 mutation status. We put forth the notion that Smurf-1 expression is stimulated by glucose, which has been confirmed to be dysregulated in the lungs of patients with IPAH (35)(36)(37)(38)(39), and may trigger the degradation of BMP-regulated Smads and reduction in Smad activation. The role of glucose in the regulation of Gremlin-1 expression in IPAH is also discussed.…”
Section: Pulmonary Arterial Hypertension (Pah)mentioning
confidence: 98%
“…PASMCs were used between passages 5 and 9 and were grown in low glucose (1 g/L) SMBM-2 media (Lonza, Walkersville, MD) supplemented with growth factors (Growth Factor Bullet Kit; Lonza) unless otherwise specified for experimental conditions as described (38).…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated glycosylation, caused mostly by failure of distinct steps in glycan formation, leads to severe morphogenic and metabolic disorders and is linked to a number of genetic diseases and cancer, 23,24 and a recent study from the Dweik group provides a strong mechanistic link between dysregulated glycosylation and PAVSMC proliferation in PAH. 25 Such a broadly shared deficit of sugars, amino sugars, and nucleotide sugars in the PAH cohort and its high dependence on mTOR activity strongly suggest that PAVSMCs in PAH have mTOR-dependent alterations of protein and lipid glycosylation that may dramatically affect multiple signaling pathways involved in disease pathogenesis.…”
Section: Sugar Metabolismmentioning
confidence: 99%